2015
DOI: 10.1149/2.0111509jss
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Water-Droplet Impacts with Velocities ofO(10 m/s) and Subsequent Flow Field

Abstract: A two-fluid spray cleaning technique has been gaining popularity as a cleaning process in the semiconductor industry. The most essential physical process in this technique is the impact of droplets with a velocity of O(10 m/s) on a solid surface. This study aims to experimentally and numerically investigate water-droplet impacts with velocities of up to 50 m/s and their subsequent flow fields, especially the gas flow field in the strictly limited area in the vicinity of the contact line. First, we experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Even in an inertia-dominant regime, the surface wettability of a horizontal plate also influences the size distribution of flowing bubbles, and alters the turbulent boundary layer structure of a bubbly mixture (Park et al [19]). For liquid droplets on, and impinging onto, solid surfaces, in the last few decades a number of researchers have reported that surface wettability strongly affects the motion of droplets and droplet-surface collisions (Chaudhury and Whitesides [20]; Fukai et al [21]; Daniel et al [22]; Tatekura et al [23]). In contrast, there are few comprehensive studies on the behavior of microbubbles along walls having different surface wettability even though engineers often experience serious difficulties in handling the behavior of microbubbles, such as microbubble-wall attachment, which eventually impacts the system's performance.…”
Section: Introductionmentioning
confidence: 99%
“…Even in an inertia-dominant regime, the surface wettability of a horizontal plate also influences the size distribution of flowing bubbles, and alters the turbulent boundary layer structure of a bubbly mixture (Park et al [19]). For liquid droplets on, and impinging onto, solid surfaces, in the last few decades a number of researchers have reported that surface wettability strongly affects the motion of droplets and droplet-surface collisions (Chaudhury and Whitesides [20]; Fukai et al [21]; Daniel et al [22]; Tatekura et al [23]). In contrast, there are few comprehensive studies on the behavior of microbubbles along walls having different surface wettability even though engineers often experience serious difficulties in handling the behavior of microbubbles, such as microbubble-wall attachment, which eventually impacts the system's performance.…”
Section: Introductionmentioning
confidence: 99%
“…We numerically investigated the liquid droplet impact pressure rise on a solid surface. We analysed the pressure generation at droplet impact by solving the two-dimensional axisymmetric compressible Euler equations [22,50]. To close the Euler equations, we implemented the stiffened-gas equation of state (2.8) in our numerical analysis; hence, we compare the pressure rise due to the liquid droplet impact obtained by numerical analysis with the stiffened-gas pressure rise Δ P sg (2.10).…”
Section: Numerical Evaluation Of the Pressure Developed Immediately Amentioning
confidence: 99%
“…Impact velocity V was set to 100 m s −1 because this order of magnitude of impact velocity can be typically observed in cleaning technologies for semiconductor device processes [23,50,58,59], in single water droplet impact experiments [11,60,61] and in numerical simulations of liquid droplet impact [9,26]. Note that the difference between c 0 and s is hardly noticeable if the value of V is much smaller, and the stiffened-gas equation of state (2.8) is not applicable if the value of V is much larger.…”
Section: Numerical Evaluation Of the Pressure Developed Immediately Amentioning
confidence: 99%
“…Shock-induced cavitation within a droplet, upon impact or interaction with a shock wave, occurs in wide range of applications, as a desired or adverse effect, ranging from raindrop impact on aircraft, 6 to combustion and detonation of multiphase mixtures, 7 through ink-jet printing or liquid jet-based physical cleaning, 8,9 to name but a few. The comprehension of the bubble dynamics within the droplet is thus of major importance to evaluate the erosion efficiency of the bubblecompounded droplet, related to the collapse and jetting processes of the cavitation bubbles.…”
Section: Introductionmentioning
confidence: 99%